2004
DOI: 10.1590/s0100-879x2004000500004
|View full text |Cite
|
Sign up to set email alerts
|

An improved HPLC method for the quantitation of 6-mercaptopurine and its metabolites in red blood cells

Abstract: A procedure is described for the rapid determination of the intraerythrocyte concentration of 6-mercaptopurine (6-MP) and its metabolites, 6-thioguanine nucleotides (6-TGN) and 6-methylmercaptopurine (6-MMP). Erythrocytes (8 x 10 8 cells) in 350 µl Hanks solution containing 7.5 mg dithiothreitol were treated with 50 µl 70% perchloric acid. The precipitate was removed by centrifugation (13,000 g) and the supernatant hydrolyzed at 100°C for 45 min. After cooling, 100 µl was analyzed directly by HPLC using a Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
(41 reference statements)
0
12
0
7
Order By: Relevance
“…The mean extraction efficiency was 87.8% for 6-MP, 90.9% for 6-TG and 92.1% for 6-MMP. Such recoveries are higher than that obtained by previous methods [1,[12][13][14][15][16][17], due to applying some modifications to the extraction process as advised by Hawwa et al [11]. Recovery seemed to increase with increasing drug concentrations, and performing a oneway ANOVA test revealed a statistically significant difference (p<0.05) between recovery % of low and high concentrations of the 3 analytes, however with no significant difference between the low/intermediate/ high concentrations.…”
Section: Recoverymentioning
confidence: 74%
See 3 more Smart Citations
“…The mean extraction efficiency was 87.8% for 6-MP, 90.9% for 6-TG and 92.1% for 6-MMP. Such recoveries are higher than that obtained by previous methods [1,[12][13][14][15][16][17], due to applying some modifications to the extraction process as advised by Hawwa et al [11]. Recovery seemed to increase with increasing drug concentrations, and performing a oneway ANOVA test revealed a statistically significant difference (p<0.05) between recovery % of low and high concentrations of the 3 analytes, however with no significant difference between the low/intermediate/ high concentrations.…”
Section: Recoverymentioning
confidence: 74%
“…Nevertheless, further experiments need to be carried out to exactly determine the causative factor. It is expected that such differences do not affect method performance as even lower recoveries are acceptable and mean values are better than other reported methods [1,[12][13][14][15][16][17].…”
Section: Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Since 6-MP is widely used in chemotherapy, it is important to develop and validate analytical methods for its determination in pharmaceutical dosage forms. Review of literature has revealed that all methods reported for the estimation of 6-MP are useful in estimating 6-MP in biological samples (Sorouraddin et al, 2011;Hawwa et al, 2009;Umrethia et al, 2006;Oliveira et al, 2004;Su et al, 1999;Mawatari et al, 1998;Sahnoun et al, 1990;Erdmann, Chan, Canafax, 1988;Rudy et al, 1988;Migulla, Prumke, Huller, 1987). So far no systematic HPLC method has been reported for determination of 6-MP in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%